Alzheimer’s Disease and Diabetes Mellitus in Comparison: The Therapeutic Efficacy of the Vanadium Compound - Zhijun He (MDPI AG, 2021)
Alzheimer’s disease (AD) is an intractable neurodegenerative disease that leads to dementia, primarily in elderly people. The neurotoxicity of amyloid-beta (Aβ) and tau protein has been demonstrated over the last two decades. In line with these findings, several etiological hypotheses of AD have been proposed, including the amyloid cascade hypothesis, the oxidative stress hypothesis, the inflammatory hypothesis, the cholinergic hypothesis, et al. In the meantime, great efforts had been made in developing effective drugs for AD. However, the clinical efficacy of the drugs that were approved by the US Food and Drug Association (FDA) to date were determined only mild/moderate. We recently adopted a vanadium compound bis(ethylmaltolato)-oxidovanadium (IV) (BEOV), which was originally used for curing diabetes mellitus (DM), to treat AD in a mouse model. It was shown that BEOV effectively reduced the Aβ level, ameliorated the inflammation in brains of the AD mice, and improved the spatial learning and memory activities of the AD mice. These finding encouraged us to further examine the mechanisms underlying the therapeutic effects of BEOV in AD. In this review, we summarized the achievement of vanadium compounds in medical studies and investigated the prospect of BEOV in AD and DM treatment.